Կարտոֆիլի որոշ սորտերի գենետիկական բազմազանությունն ըստ կենսաքիմիական և մոլեկուլային մարկերների 232 - Բադալյան, Մանվել; Ալոյան, Տաթևիկ; Մելիքյան, Անդրեաս (ՀԱԱՀ հիմնադրամ)
As a globally important food crop, the potato ranks fourth in production, following wheat, rice, and maize. Currently, over 7,000 varieties, developed in the 18th and 20th centuries, are cultivated worldwide. At this stage of agricultural development, where the primary challenge is the creation of new crop varieties and the improvement of existing ones to meet growing population and production demands, both classical breeding methods and modern technologies — such as molecular markers and genetic transformation — are employed. This study investigates the intravarietal and intervarietal diversity of three valuable potato varieties cultivated in Armenia. Genetic polymorphism was assessed using protein markers (11S-globulin protein profiles and electrophoretic spectra) and DNA markers (RFLP). The research utilized a combination of classical agronomic, molecular biological, biotechnological, and genetic-mathematical methods. The results revealed that the 11S-globulin proteins in all studied potato varieties exhibit polymorphism, as evidenced by distinct electrophoretic spectra and protein profiles. Additionally, the DNA restriction fragment patterns showed varying lengths within the same variety, indicating significant intravarietal genetic polymorphism. These findings can serve as genetic markers for the identification and passporting of the studied varieties, as well as for marker-assisted selection in breeding programs. На современном этапе развития сельского хозяйства, когда первостепенными задачами являются получение новых сортов сельскохозяйственных культур и улучшение уже существующих, наряду с классической селекцией используются новейшие технологии, в том числе молекулярные маркеры и генетические трансформации. В рамках данного исследования было изучено внутрисортовое и межсортовое разнообразие трех ценных сортов картофеля, возделываемых в Армении. Полученные результаты могут быть использованы в качестве генетических маркеров при идентификации, паспортизации указанных сортов, а также при проводимой в отрасли маркерной селекции.
Keywords: Ագրոնոմիա